2019
DOI: 10.18535/ijsrm/v7i5.el03
|View full text |Cite
|
Sign up to set email alerts
|

The effect of integration electronic mind maps into Arabic language vocabulary’s lecture on achievements of fifth-grade students in Jordan

Abstract: The study was conducted to investigate the integration of electronic mind map within the Arabic vocabulary instruction for fifth-grade students at Jordan. The sample included two classes chosen by the available method from the fifth grade classes in two schools in northern Jordan. One of the classes (29 pupils) whom represented the experimental group; its members studied using the strategy of Electronic Mind map. The other class (30 pupils) represented the control group. The researchers used an achievement tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The mean score of the Control Group was the lowest (M = 5.51; SD = 2.03). The findings of the MANCOVA test in Table 4.1 demonstrated that there is a significant difference between the Experimental Group 1, Experimental Group 2 and Control Group in their mean score for multiple-choice questions for comprehension in the Post-test (F = 81.71, These results clearly support the findings by Alomari (2019) which showed that utilizing of Bubble Map and Tree map methods had significantly improved the mean score of students in MCQ compared with the Control Group. These findings are in line with findings by Saori (2020) which indicated that the use of Bubble Map and Tree Map methods were effective in promoting students' critical thinking skills and stimulate them to answer the comprehension questions.…”
Section: Rq1supporting
confidence: 73%
See 1 more Smart Citation
“…The mean score of the Control Group was the lowest (M = 5.51; SD = 2.03). The findings of the MANCOVA test in Table 4.1 demonstrated that there is a significant difference between the Experimental Group 1, Experimental Group 2 and Control Group in their mean score for multiple-choice questions for comprehension in the Post-test (F = 81.71, These results clearly support the findings by Alomari (2019) which showed that utilizing of Bubble Map and Tree map methods had significantly improved the mean score of students in MCQ compared with the Control Group. These findings are in line with findings by Saori (2020) which indicated that the use of Bubble Map and Tree Map methods were effective in promoting students' critical thinking skills and stimulate them to answer the comprehension questions.…”
Section: Rq1supporting
confidence: 73%
“…This leads them to stay focus for a longer period of time and the learning process is enjoyable. Alomari (2019) assessed the effectiveness of mind mapping to develop students' reading comprehension in Jordan. The sample of the study consisted of 65 students using quasi-experimental design.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Moreover, one of the most S. R. Sharif, C. K. S. Singh, E. T. Ong, D. Mulyadi, I. Z. Ichsan, H. Rahmayanti & T. Kiong, The use of i-THINK Mapping in teaching reading comprehension among ESL teachers | 91 important aspects of the i-THINK maps is the students' ability to display thinking skills to complete the maps (Alomari, 2019). Research conducted by Hassan et al (2016) on 11th-grade students found that the thinking levels of analysing and synthesising were the strengths of the concept map while a particular strategy also strengthened students' mastery of information on HOTS (Awofala, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It also has a great impact on reading comprehension. Using mind maps to help students learn English more effectively is a new means of modern English Teaching Model [12].…”
Section: Communicative Approachmentioning
confidence: 99%